Kewenangan Pemerintah Kabupaten/Kota Dalam Menyelenggarakan Pelayanan Publik Guna Meningkatkan Pemenuhan Kebutuhan Layanan Masyarakat - Andika Dwi Yuliardi; Maharani Nurdin (Jurnal Hukum Sasana, 2023)
The granting of regional autonomy in public services can realize equal distribution of rights received by the entire community and as a form of responsibility for local governments. For this reason, the government delegates its authority to the regions (provinces, districts and cities). However, there are still monotonous public services with snaking service queues and inadequate facilities, this indicates a lack of local government governance. The problem in this research is how to regulate and apply the authority of district/city governments in providing public services and what are the driving factors for district/city governments in providing public services so that community service needs can be met. The method in this study uses a normative juridical research type, namely research that focuses on studying the application of norms or rules in positive law. The results of the study indicate that the implementation of public services must be emphasized on a number of aspects, including: speed; accuracy; convenience; and justice. Therefore, a full contribution from the district/city government is needed so that public services can run well so that the rights of all people can be guaranteed.